Aplikasi Alat Bantu Pembelajaran Matematika Untuk Siswa Kelas II Sekolah Dasar Berbasis Web - Tias, Heraly Winahyu Cahyaning, Hernawan Sulistyanto, S.T., M.T (2017)
Mathematic is one of the most important lesson and being learned in all fields. But there are many of second grade elementary student who thinks that mathematic is difficult. So, in order to solve the said problem, the needed of computer web based media learning is important, it helps the learning process become more innovative and interactive that student can be more active and enthusiast to learn mathematic. The research method that used to build the application is an action research methods class the computer media learning with web based will be built using HTML, PHP and CSS. This research resulted in an application of mathematics teaching aids for second grade elementary student based web.